CLASSIFICATION OF TOURISM SMEs - ERDOĞAN, Yakup (Selcuk University, 2022)
SMEs, which are extremely important for national economies, are supported by both developed and developing countries due to their advantages. The evaluation of touristic enterprises as "SMEs" in the five-year development plans has enabled tourism enterprises to benefit from these supports and economic aids. The definition of SME may vary between countries and even between institutions and organizations within the same country. Among the reasons for this change are the differences in the criteria used for measurement such as production, marketing, sales volume, number of employees and amount of capital. The aim of this study is to reveal how SME classifications are made in Turkey and European Union member countries. The data within the scope of the study were collected by document analysis method. The general scanning model was preferred as the research design. It has been observed that criteria such as the number of employees, budget volume and sales volume are used in making the classifications. Considering the accommodation establishments in particular, it is understood that the classification is made according to the number of rooms and employees. In this study, attention was drawn to the extent to which SMEs dominate the market, how important they are for the country's economies, and the economic support to be given according to these classifications.
Keywords: Turizm; Turizm (Diğer); Classification; SMEs; Tourism; Tourism (Other); SMEs; Sınıflandırma; KOBİ; Turizm; Classification; KOBİ; Tourism; Sınıflandırma; 1. No poverty; 8. Economic growth; 11. Sustainability